Large Cell Neuroendocrine Carcinoma of Lung metastasizing to Jejunum – A rare presentation with review of Literature - Gupta, Amit; Tandon, Ashutosh; Kumar, Abhay; Kumar, Sunil; Singh, Usha Rani (Asian Journal of Medical Sciences, 2013)
Large cell neuroendocrine carcinoma of lung is not one of the commoner varieties of neoplasia found in the lungs. There are around 100 cases in literature which suggest the metastasis of various kinds of lung carcinomas to gastro intestinal tract (GIT). Metastasis of large cell neuroendocrine carcinoma to small bowel is rare. This is a rare case in which the primary neuroendocrine carcinoma of lung presented with metastasis and perforation of small bowel. DOI: http://dx.doi.org/10.3126/ajms.v4i2.5370 Asian Journal of Medical Sciences 4(2013) 47-50